2016
DOI: 10.1186/s13089-016-0046-8
|View full text |Cite|
|
Sign up to set email alerts
|

12th WINFOCUS world congress on ultrasound in emergency and critical care

Abstract: Purpose: Cervical traumas are frequent in emergency department and X-ray, CT, and MRI are the essential imaging modalities in the diagnosis. However, especially for pregnant and morbid obese patients and children, these techniques can be challenging. We tested the success of point-of-care ultrasound in the evaluation of cervical traumas. Methods: This is a case series of cervical vertebra imaging with ultrasound in emergency department. We used linear probe and placed it anterolaterally to the neck, parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The use of PoCUS is growing rapidly and being performed by physicians in various specialties for a wide range of applications . PoCUS is defined as a limited scan performed to answer a specific clinical question, enabling fast‐tracked patient management .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PoCUS is growing rapidly and being performed by physicians in various specialties for a wide range of applications . PoCUS is defined as a limited scan performed to answer a specific clinical question, enabling fast‐tracked patient management .…”
Section: Introductionmentioning
confidence: 99%
“…The use of PoCUS is growing rapidly and being performed by physicians in various specialties for a wide range of applications. [1][2][3][4][5] PoCUS is defined as a limited scan performed to answer a specific clinical question, enabling fast-tracked patient management. 2 Ultrasound has been hailed as the new 'visual stethoscope' of the twenty-first century, providing a valuable clinical tool for more accurate patient assessment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common type of fractures in children are those of the forearm, followed by the humerus and phalanges. Ultrasound guided manipulation and reduction of these fractures is recommended in literature [ 50 ] as it has been shown to reduce the need for repeated radiographs, sedation, and as it is associated with lower levels of pain and higher caregiver satisfaction [ 51 , 52 ]. The ability of ultrasound to identify subperiosteal hematoma makes this procedure particularly valuable in the early recognition of possible abusive skeletal injury [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that clinicians are uncomfortable with their level of skill using PoCUS and would be interested in improving their skills . Moreover, confidence in the use of ultrasound appears to wane over time, possibly from lack of use or ongoing training . The efficacy of training programmes for students, residents and non‐clinicians such as nurses and midwives in the use of PoCUS has been explored extensively in the literature.…”
Section: Pocus Training In Australia and Worldwidementioning
confidence: 99%